Studying the Properties of RF-Sputtered Nanocrystalline Tin-Doped Indium Oxide. (29th May 2011) - Kashyout, Abd El-Hady B.; Fathy, Marwa; Soliman, Moataz B.
Abstract : The ceramic target of Indium tinoxide (ITO) (90% In2 O3 -10%SnO2 ) has been used to prepare transparent semiconductive thin films on glass substrate by RF magnetron sputtering at room temperature. The properties of the thin films are affected by controlling the deposition parameters, namely, RF power values and deposition times. The structure, morphology, optical and electrical properties of the thin films are investigated using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), atomic force microscope (AFM), UV-Vis spectrophotometer, and four-point probe measurement. Nanoparticles of 10–20 nm are measured and confirmed using both FESEM and AFM. The main preferred orientations of the prepared thin films are (222) and (400) of the cubic ITO structure. The transparent semiconductive films have high transmittance within the visible range of values 80–90% and resistivity of about1.62 × 10 − 4 Ω·cm.